ÁMBITOS Y ALCANCES DE LA COMPETENCIA COMUNICATIVA EN EDUCACIÓN - Montalvo, Jorge Abelardo Cortés; Uribe, Rigoberto Marín; Ibarra, Isabel Guzmán (European Scientific Journal, ESJ, 2013)
In the environment of competency based educational models in Mexican public universities, outstands for its generic and crossing role, as an important and essential vector and condition in order to develop any other competency, the communicative competency. However, the definition of communicative competency is still considered limited, partial and linear, and it is reduced to its transmitter and receptive acceptance regarding to its linguistic and straight forward definition. This paper explains how the communicative competency is re-dimensioned and identified by, at least, five different areas, four of those areas have an instrumental role; of course it has to do with acquisition, management and use of diverse languages, but also, include some aspects associated with techno-competency, info-competency, media-competency, and the ethicemotional role which communicative competency contains, this last one mentioned, is not instrumental. Every single of communication competency aspect related closely to teaching experience.